Peradaban Islam pada Masa Khilafah Al-Rasyidah - Chindy Shamantha (Fakultas Agama Islam Universitas Singperbangsa Karawang, 2023)
The teachings of the caliphate in the Qur'an are that everything that exists in this world, both in the form and in human potential, is only a gift from Allah SWT. The four caliphs in Islamic history are called al-rasyidin hulefaur. Based on this, the author tries to discuss the leadership of the Rashidun Khulafaur. (2) to find out who the Rashidun Khulafah were, and (3) to find out the development of Islam as a political force. The research method used in this research is historical research method. The results of this study are first, the history of Islamic civilization during the al-Kulafa era, then who the Rashidun Caliphate was and the development of Islam in political power.